The earth, my butt, and other big round things - Mackler, Carolyn (Cambridge, MA : Candlewick Press, 2003)
Feeling like she does not fit in with the other members of her family, who are all thin, brilliant, and good-looking, fifteen-year-old Virginia tries to deal with her self-image, her first physical relationship, and her disillusionment with some of the people closest to her.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
5.3
Young Adult
Keywords: Assertiveness (Psychology) -- Fiction; Family problems -- Fiction; High schools -- Fiction; Schools -- Fiction; Self-perception -- Fiction; Weight control -- Fiction; Assertiveness (Psychology) -- Fiction; Family problems -- Fiction; High schools -- Fiction; School stories; Self-perception -- Fiction; Weight loss -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction